Contrasting defence mechanisms against spider mite infestation in cyanogenic and non-cyanogenic legumes - Boter, Marta (Plant science : an international journal of experimental plant biology, 2024)
Copyright © 2024 The Authors. Published by Elsevier B.V. All rights reserved.